Investigating The Influence of Teacher Aggression on Student Academic Motivation in Province of Sindh, Pakistan - Ahmed, Maroof; Soomro, Aizaz Ali; Haleema, Haleema (IJELR: International Journal of Education, Language, and Religion, 2023)
The present study aimed to explore the impact of teacher aggressive behaviors on student academic motivation in Sindh, one of the provinces in Pakistan. A descriptive survey research design was employed, utilizing a sample of 120 public school teachers (70 female and 50 male). Data was collected using a researcher-developed instrument called the "Teachers Aggressive Behavior Survey" (TABS). The research questions were answered using descriptive statistics, including means and standard deviations, and the hypothesis was tested using t-test statistics at a significance level of 0.05. The results indicated that teachers exhibit various forms of aggressive behaviors that negatively impact student participation in academic activities. It is recommended that school administrators take steps to raise awareness among teachers about the detrimental effects of aggressive behaviors on student academic motivation.